Novel nicotinamide analog as inhibitor of nicotinamide N-methyltransferase - Ruf, Sven; Kannt, Aimo (Bioorganic & medicinal chemistry letters, 2018)
Nicotinamide N-methyltransferase (NNMT) has been linked to obesity and diabetes. We have identified a novel nicotinamide (NA) analog, compound 12 that inhibited NNMT enzymatic activity and reduced the formation of 1-methyl-nicotinamide (MNA), the primary metabolite of NA by ∼80% at 2h when dosed in mice orally at 50mg/kg.